2010
DOI: 10.1063/1.3360812
|View full text |Cite
|
Sign up to set email alerts
|

Droplet electric separator microfluidic device for cell sorting

Abstract: A simple and effective droplet electric separator microfluidic device was developed for cell sorting. The aqueous droplet without precharging operation was influenced to move a distance in the channel along the electric field direction by applying dc voltage on the electrodes beside the channel, which made the target droplet flowing to the collector. Single droplet can be isolated in a sorting rate of ∼100 Hz with microelectrodes under a required pulse. Single or multiple mammalian cell (HePG2) encapsulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 18 publications
2
63
0
Order By: Relevance
“…Another recent study carried out by Guo et al [59] has demonstrated sorting of water droplets in oil using electrophoresis. It was reported that this method allows to achieve considerably higher throughput in continuous flow.…”
Section: Electric Forcementioning
confidence: 99%
“…Another recent study carried out by Guo et al [59] has demonstrated sorting of water droplets in oil using electrophoresis. It was reported that this method allows to achieve considerably higher throughput in continuous flow.…”
Section: Electric Forcementioning
confidence: 99%
“…The amazingly fast development of lab-on-a-chip technology in recent decades has had a profound impact on the food and healthcare industries [1]- [3], as well as novel applications in bio-defense against bioterrorism and bio-warfare [4]. Many experimental techniques for microparticle manipulation have been extensively reported in prior studies, such as using biochemical [5], electrokinetic [6], optical [7], and magnetic [8] methods. Compared to these conventional techniques, another popular method that utilizes acoustics to drive microfluidic actuation has shown distinct advantage as an easy tool for manipulation of colloidal particles [9]- [11].…”
Section: Rf-activated Standing Surface Acoustic Wavementioning
confidence: 99%
“…Substituting (5) into (1), the acoustic radiation force on a rigid sphere can then be obtained, (6) For a very small compressible spherical particle , the time-averaged acoustic radiation force has been derived by Eller [25], (7) where is the instantaneous particle volume. For a small sphere, can be written as [25] …”
Section: A Dynamics Of Particle Aggregation Under Ssawmentioning
confidence: 99%
“…As an important branch of microfluidics, droplet-based microfluidics own innate advantages in biochemical assays. The droplet is a separate, micro-sized reaction chamber, which makes it possible to minimize the energy consumption and the required reagents, and to better control the mixture/reaction parameters [19][20][21][22]. While, to our best knowledge, there is little work on utilizing droplet-based microfluidic systems for Hg(II) ion detection.…”
Section: Introductionmentioning
confidence: 99%